2023
DOI: 10.1002/ana.26585
|View full text |Cite
|
Sign up to set email alerts
|

Ultrastructural Axon–Myelin Unit Alterations in Multiple Sclerosis Correlate with Inflammation

Abstract: Objective: Changes in the normal-appearing white matter (NAWM) in multiple sclerosis (MS) may contribute to disease progression. Here, we systematically quantified ultrastructural and subcellular characteristics of the axon-myelin unit in MS NAWM and determined how this correlates with low-grade inflammation. Methods: Human brain tissue obtained with short postmortem delay and fixation at autopsy enables systematic quantification of ultrastructural characteristics. In this study, we performed high-resolution i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
2

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 48 publications
(114 reference statements)
0
13
2
Order By: Relevance
“…36 Our myelin blister results further support the prelesional/early lesional nature of mDAWM. Myelin blisters are emerging as important MS pathology correlates, being spotted in several NAWM and peri-lesion areas of MS brains 5 and, more recently, in the optic nerve, 33 a region often associated with the earliest MS lesion formation. 42 Nonetheless, in line with the early involvement of myelin blisters in lesion formation, studies employing cuprizone mouse models of MS have reported the presence of similar morphological alterations in mice weeks prior to demyelination.…”
Section: Discussionmentioning
confidence: 99%
“…36 Our myelin blister results further support the prelesional/early lesional nature of mDAWM. Myelin blisters are emerging as important MS pathology correlates, being spotted in several NAWM and peri-lesion areas of MS brains 5 and, more recently, in the optic nerve, 33 a region often associated with the earliest MS lesion formation. 42 Nonetheless, in line with the early involvement of myelin blisters in lesion formation, studies employing cuprizone mouse models of MS have reported the presence of similar morphological alterations in mice weeks prior to demyelination.…”
Section: Discussionmentioning
confidence: 99%
“…Nodal and paranodal regions have been considered particularly vulnerable sites of immune-mediated injury in MS ( 15 ). Alterations in these regions can even be observed in normal-appearing white matter ( 16 , 17 ) and are implicated in contributing to disease progression in MS ( 17 ). Ultrastructure changes include uncompacting of myelin, unmasking of potassium channels, and increased axonal energy demand.…”
Section: Early Events In Multiple Sclerosis Drive Disabilitymentioning
confidence: 99%
“…The WM tissue of stroke brain donors did not contain infarcts. Cryo-protected frozen optic nerve samples of MS (n=4) and control donors (n=4) were previously obtained 29 .…”
Section: Post-mortem Brain Tissue Selection For Ldm and Ihcmentioning
confidence: 99%
“…For IHC, (NA)WM tissue of MS (n=9) and stroke (n=8) brain donors was cut from frozen (20 µm) or paraffin-embedded (8 µm) tissue blocks not containing any lesions or reactive sites. For SMI312 and PLP, normal-appearing optic nerve tissue of MS donors was fixed overnight in 4% paraformaldehyde, protected in 30% sucrose for 24 hours, frozen, and cut at 20 µm 29 . For paraffin-embedded tissue, antigen retrieval was performed as indicated in Table 3 for 10 min in a microwave at 700 W. Sections were incubated overnight at 4°C with primary antibodies (Table 3) diluted in incubation buffer (for paraffin tissue: 0.5% gelatin and 0.5% Triton X-100 in TBS; for frozen tissue: 1% bovine serum albumin and 0.5% Triton X-100 in phosphate-buffered saline, pH7.6).…”
Section: Immunohistochemistrymentioning
confidence: 99%